EVALUATION OF THE ROLE OF PRINCIPAL LEADERSHIP IN IMPROVING TEACHER MOTIVATION - Risnawati LUBIS; Yessy Yanita SARI (Journal of Education and Leadership in Education, 2018)
Evaluation of Principal's Leadership Role in Improving Teacher's motivation at Yayasan Al Hidayah Lebak Bulus, South Jakarta. Thesis. Educational Administration Study Program. School of Postgraduate Study University of Muhammadiyah Prof. Dr. HAMKA. August 2016. The purpose of this research was to obtain information and evaluate the effectiveness of Principal's Leadership Role at Junior High School and Vocational High School Al Hidayah in increasing motivation and expected to contribute in running the leadership wheel of the principal. The method used is a qualitative method with a discrepancy evaluation model (DEM). The approach used is a qualitative approach. Data collection techniques by observation, interviews, and FGD (forum group discussion). The results of this evaluation concluded that the Principal's Leadership Role had not run in accordance with the principal's leadership standards in carrying out its role. Many aspects and focus of evaluation require improvement and improvement to achieve maximum results in terms of Principal’s Leadership Role in carrying out its roles and functions. This research recommends to all parties involved to optimize the leadership role of the head of the school in carrying out their duties and functions optimally for the progress of the school or foundation.